Context-Dependent Preferences in Starlings: Linking Ecology, Foraging and Choice - Vasconcelos, Marco (Public Library of Science, 2013)
Foraging animals typically encounter opportunities that they either pursue or skip, but occasionally meet several alternatives simultaneously. Behavioural ecologists predict preferences using absolute properties of each option, while decision theorists focus on relative evaluations at the time of choice. We use European starlings (Sturnus vulgaris) to integrate ecological reasoning with decision models, linking and testing hypotheses for value acquisition and choice mechanism. We hypothesise that options' values depend jointly on absolute attributes, learning context, and subject's state. In simultaneous choices, preference could result either from comparing subjective values using deliberation time, or from processing each alternative independently, without relative comparisons. The combination of the value acquisition hypothesis and independent processing at choice time has been called the Sequential Choice Model. We test this model with options equated in absolute properties to exclude the possibility of preference being built at the time of choice. Starlings learned to obtain food by responding to four stimuli in two contexts. In context [AB], they encountered options A(5) or B(10) in random alternation; in context [CD], they met C(10) or D(20). Delay to food is denoted, in seconds, by the suffixes. Observed latency to respond (L(i)) to each option alone (our measure of value) ranked thus: L(A)≈L(C)<L(B)<<L(D), consistently with value being sensitive to both delay and learning context. We then introduced simultaneous presentations of A(5) vs. C(10) and B(10) vs. C(10), using latencies in no-choice tests to predict sign and strength of preference in pairings. Starlings preferred A(5) over C(10) and C(10) over B(10). There was no detectable evaluation time, and preference magnitude was predictable from latency differentials. This implies that value reflects learning rather than choice context, that preferences are not constructed by relative judgements at the time of choice, and that mechanisms adapted for sequential decisions are effective to predict choice behaviour.